Analisisis Assesmen Autentik Pembelajaran Matematika Sekolah Dasar - AM. Mega Purnamatati Mega; Faisal Madani (Elementary Teacher Education Program, Majalengka University, 2023)
Learning and assessment are inseparable parts because educators and students need to understand the intended competencies so that the planning, process, and evaluation of learning can be attempted by educators to achieve these competencies. Elementary School Mathematics” which is about (1) the implementation of authentic assessments of elementary school mathematics learning; (2) The benefits of authentic assessment of elementary school mathematics learning; (3) The impact of an authentic assessment of elementary school mathematics learning. This research uses a qualitative method with a case study approach. The data collection techniques used in this study were interviews and observations of 6 teachers from two different schools, namely SDN LULUT 05 and SDN LULUT 02, in this study, it was found that each teacher had their way of implementing authentic assessments in learning elementary school mathematics which is adjusted to what will be measured (cognitive, affective, psychomotor aspects), learning outcomes, learning objectives and materials, assessments or assessments of students in the learning process are of increasing quality. And the positive impact obtained increases learning motivation improves the quality of learning, fosters critical thinking skills and analysis, and improves students' ability to solve problems related to mathematics.